An analysis of moves and first-person references in Indonesian hotel responses to online positive reviews - Cita Nuary Ishak; M. Adieb Hidayatullah (Studies in English Language and Education, 2022)
Technology advancements have allowed customers to post their reviews on online platforms. In the hotel industry, responding to positive and negative reviews is imperative because it helps hotels maintain their relationship with past customers and establish a positive online persona. This paper examined the generic structure of Indonesian hotel responses to positive reviews (RPRs) through move-step and first-person reference analysis. For this purpose, we compiled a corpus of 87 authentic hotel responses to positive reviews written by past customers on TripAdvisor. The results revealed that the generic structure of this genre consists of five major moves (opening, thanking or appreciating, acknowledging a message, ending, and closing) and a minor move (positive small talk). Unique to these findings is the positive small talk, which includes explicit hopes for customers’ satisfaction and the use of phrases such as ‘your second home’ and ‘one big family’ when referring to the hotels. Regarding the first-person reference, hotel representatives tended to use the plural pronoun ‘we,’ reflecting a cooperative identity. The exclusive ‘we’ serves various communicative functions in the hotel RPRs. However, it is mainly typical of three major moves and steps: thanking or appreciating the positive reviews and the stay, stating the hotels’ commitment and standard, and soliciting a return visit. These findings can be of use as an alternative model to which practitioners in the hotel industry, including students of business English and ESP courses, may refer when aiming to produce texts within this genre.